Let , and be the solutions of the simultaneous equations Then the three roots of the cubic equation are , and , where . What is the value of ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
⎩ ⎪ ⎨ ⎪ ⎧ x + y + z = − 7 1 → ( 1 ) 4 x + 2 y + z = − 3 2 → ( 2 ) 9 x + 3 y + z = − 2 7 → ( 3 ) ( 2 ) − ( 1 ) ( 4 x + 2 y + z ) − ( x + y + z ) = − 3 2 − ( − 7 1 ) 3 x + y = 3 9 → ( 4 ) ( 3 ) − ( 1 ) ( 9 x + 3 y + z ) − ( x + y + z ) = − 2 7 − ( − 7 1 ) 8 x + 2 y = 4 4 → 4 x + y = 2 2 → ( 5 ) ( 5 ) − ( 4 ) ⟹ ( 4 x + y ) − ( 3 x + y ) = 2 2 − 3 9 x = − 1 7 x = − 1 7 ⟹ 4 x + y = 2 2 → 4 ( − 1 7 ) + y = 2 2 y = 2 2 + 6 8 = 9 0 → y = 9 0 x + y + z = − 7 1 − 1 7 + 9 0 + z = − 7 1 z = − 7 1 − 7 3 = − 1 4 4 Hence ( a , b , c ) = ( − 1 7 , 9 0 , − 1 4 4 ) .Hence the cubic equation is: t 3 − 1 7 t 2 + 9 0 t − 1 4 4 = 0 By the Rational Root Test, t = 3 is a solution.Dividing y t − 3 gives t 2 − 1 4 t + 4 8 ,which nicely factors into ( t − 8 ) ( t − 6 ) .Hence t 3 − 1 7 t 2 + 9 0 t − 1 4 4 = ( t − 3 ) ( t − 6 ) ( t − 8 ) .Since α < β < γ , α = 3 , β = 6 , γ = 8 .Hence, 1 0 0 α + 1 0 β + γ = 1 0 0 ( 3 ) + 1 0 ( 6 ) + 8 = 3 6 8